2020
DOI: 10.3390/ijms21072318
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Use of Extracellular Vesicles for Acute and Chronic Lung Disease

Abstract: Multipotent mesenchymal stem cells (MSCs) possess regenerative properties and have been shown to improve outcomes and survival in acute and chronic lung diseases, but there have been some safety concerns raised related to MSC-based therapy. Subsequent studies have demonstrated that many of the regenerative effects of MSCs can be attributed to the MSC-derived secretome, which contains soluble factors and extracellular vesicles (EVs). MSC-derived extracellular vesicles (MSC-derived EVs) replicate many of the ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 75 publications
(91 reference statements)
0
77
0
Order By: Relevance
“…Luckily, stem cells and their extracellular vesicles are able to repair the damage and relieve lung symptoms, thus they have been used to cure ARDS. 103 Currently, some COVID-19 patients have been treated with umbilical cord mesenchymal stem cells and achieved good effects. 104 Therefore, stem cells may be the hope for the treatment of severe COVID-19 patients.…”
Section: Remediesmentioning
confidence: 99%
“…Luckily, stem cells and their extracellular vesicles are able to repair the damage and relieve lung symptoms, thus they have been used to cure ARDS. 103 Currently, some COVID-19 patients have been treated with umbilical cord mesenchymal stem cells and achieved good effects. 104 Therefore, stem cells may be the hope for the treatment of severe COVID-19 patients.…”
Section: Remediesmentioning
confidence: 99%
“…The progression of COVID-19 leads to the development of pulmonary diseases, such as idiopathic pulmonary fibrosis or ARDS, commonly associated with damage to alveolar epithelial cells, which in turn is related to a severe hypoxia of the alveolar cells, leading to a massive apoptosis, therefore, contributing to the pathophysiology of lung fibrosis[ 49 ]. Experimental studies have indicated that not only MSCs but also their derivates, such as a conditioned medium containing a variety of bioactive factors or extracellular vesicles (EVs) (microvesicles and exosomes) carrying various cytoplasmic components, including lipids, DNA fragments, and RNA (including mRNA and microRNA), contribute to the recovery of alveolar epithelial cells and endothelial cells and modify the function of inflammatory infiltrates in paracrine and endocrine manners[ 50 , 51 ].…”
Section: Mscs As Supportive Therapy In Covid-19 Patientsmentioning
confidence: 99%
“…These studies have further confirmed that post-exosomal infusion, the associated cytokine storm and pro-inflammatory signalling biomolecules were considerably reduced that were primarily responsible for ARDS pathogenesis [ 46 ]. Further analysis confirmed that the exosomes also increased the level of anti-inflammatory signalling mediators that can reduce the severity of the lung injury through increase permeability and functional aspects of alveolar epithelium [ 47 , 48 ],…”
Section: Introductionmentioning
confidence: 99%